2015
DOI: 10.1089/vim.2014.0147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Risk Factors on Anti-HBs Development in Hepatitis B Vaccinated and Nonvaccinated Populations

Abstract: Hepatitis B infection is still a major global health problem even though safe and effective vaccines have been available for more than 30 years. Although development of protective antibody to hepatitis B surface antigen (anti-HBs) is a common phenomenon after vaccination as well as natural infection, sometimes it does not appear even after complete vaccination. In the present study, whether the impairment of the development of anti-HBs in naturally infected and/or vaccinated populations is associated with immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…Hepatitis B virus (HBV) infects over 350 million people globally per year and causes serious acute and chronic liver diseases (Mast et al 2005 ; Norder et al 1993 , 1994 ). Globally, more than 300 million people have chronic HBV infection and approximately two billion are infected (Scheiblauer et al 2010 ; Shaha et al 2015 ). HBV integrates its genome into liver cell and can reside there for long time which is seem to develop HBV carrier state and thereby, may cause damage to the liver permanently (Suppiah et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infects over 350 million people globally per year and causes serious acute and chronic liver diseases (Mast et al 2005 ; Norder et al 1993 , 1994 ). Globally, more than 300 million people have chronic HBV infection and approximately two billion are infected (Scheiblauer et al 2010 ; Shaha et al 2015 ). HBV integrates its genome into liver cell and can reside there for long time which is seem to develop HBV carrier state and thereby, may cause damage to the liver permanently (Suppiah et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only six studies reported the prevalence of anti-HBc among healthy population groups [3-4, 11, 15, 19, 23], and the range varies from around 10% to upwards of 60% ( Figure 2). Considering how neither of the two studies documenting highest [19] and lowest [4] prevalence represent the general population accurately (Figure 2), the actual range would probably be a lot tighter. For the remainder of our analysis, we will use the prevalence rates derived using HBsAg.…”
Section: Choice Of Biomarkersmentioning
confidence: 99%
“…The strategy in many countries today is to reject anti-HBc positive blood[57]. However, due to the relatively high endemicity of Hepatitis B in Bangladesh (recent prevalence rates being as high as 60% in certain risk groups[19], this step would be hardly practical as it would drastically reduce the viable blood donorpopulation. Short of adopting Nucleic Acid Testing (NAT) as a part of the screening program, Jahan et al recommends excluding anti-HBc positive patients with heightened levels of ALT [63].…”
mentioning
confidence: 99%
“…Alguns estudos estabelecem como possíveis causas para a não soroconversão em indivíduos completamente vacinados contra hepatite B, o tabagismo e a obesidade, condições presentes no estilo de vida de alguns trabalhadores da saúde. 21,22 Entretanto, de modo similar ao percentual de cobertura vacinal, a porcentagem de profissionais que checam suas condições sorológicas pós-vacinação varia conforme o país de origem desses trabalhadores. 23,24 Um estudo revelou que os trabalhadores da saúde frequentemente não executam, após a vacinação, o teste anti-HBs.…”
Section: Agradecimentosunclassified